Online Resources. - Elwell, Sage (Religious Studies Review (John Wiley & Sons, Inc.), 2023)
The article focuses on various online platforms catering to the study of religion, encompassing both scholarly research and pedagogical resources, including the websites such as The Immanent Frame, The Religious Studies Project, each offering distinct content such as essays and podcasts.